OBTAINING OF FUNGAL BIOCOMPOUNDS BY SOLID STATE FERMENTATION (Revista CIATEC-UPF, 2021)
The cultivation of microorganisms to obtain biosurfactants and lipases using solid-state fermentation (SSF) is considered a sustainable and low-cost form. The simultaneous production of these biocompounds is still little explored, especially when using solid matrices as a substrate aiming at reducing residues and environmental impacts and the potential environmental application of the produced biocompounds, in bioremediation processes and effluent treatment. The aim was the simultaneous production of lipases and biosurfactants via SSF from the fungus Aspergillus niger. Screening of cultivation media and conditions was carried out, with the studied variables being the proportions of soybean meal (SM) and soybean waste (SW), moisture, concentrations of carbon source (molasses), oily inducer and nitrogen source, through experimental designs. The media were fermented for 6 days, evaluating the lipase and emulsifying activities and the reduction in surface tension obtained every 2 days. In the culture medium composed of SM + SW (70/30), production of lipases (31.13 ± 0.55 U) and biosurfactants (11,92 % of reduction of surface tension and emulsifying activity below 2.00 EU) was observed under conditions of 50% of moisture, 1.5% of nitrogen source and 1% of oily inducer.